Pelaksanaan Perjanjian Bagi Hasil Gaduh Pemeliharaan Hewan Ternak Berdasarkan Hukum Adat( Studi Kasus Di Desa Temboro Kecamatan Karang Tengah Kabupaten Wonogiri Tahun 2016 ) - IRAWAN, IRAWAN; , Drs. Hj. Sri Arfiah, SH, M.Pd (2017)
This research aims to. First describe the implementation of revenue-sharing agreements gaduh maintenance of livestock by customary law in the village Temboro covers the background of the agreement, the form of revenue sharing agreements, rights and obligations of the agreement, the term of the agreement, the settlement of the conflict. Both describe the constraints in the implementation of revenue-sharing agreements gaduh. The third describes the solutions to overcome obstacles in the implementation of revenue-sharing agreements gaduh. This study is a qualitative research that is descriptive. Sources of data obtained from several informants (Informants were selected in this study include: Owners of livestock in the village and Penggaduh Temboro), places and events, as well as documents. Data collection techniques used in this study were interviews, observation, and documentation. This study uses the triangulation of data sources. Data analysis technique used is interactive analysis. Results of the first study showed that the implementation of revenue-sharing agreements based on the background of the agreement, which is done on the basis of mutual help and kinship. Both forms of agreement, which is based on mutual agreement between the owner and penggaduh. Thirdly rights and obligations of the agreement, which according to the agreement that has been determined. The fourth term of the agreement, not specified expiry time. Fifth of conflict resolution, with deliberation of kinship. The problem is when the process penggaduhan livestock ill and no one died. The solution is settled amicably kinship.